IMPLIKASI EKONOMI ATAS OPINI PENILAIAN PENGELOLAAN KEUANGAN DAERAH - Didik Susetyo (Department of Development Economics, Universitas Sriwijaya, 2009)
Aimed of this study is to know implication result of audit categories in implementing of local budget in South Sumatra. This study focused on several two years between 2004 and 2007. Analysis method used is a qualitative description by figuring cross tabulation and comparing highest-lowest indicators of audit categories. Result of this study can be identified relating to some implications such as: (1) entities of the departments and institutions tended to be better; (2) part of the entity of local budget were getting better, but part of entity were getting worst; (3) nine of the entity in South Sumatra got qualified opinion (WDP). It means that the local governments have not implemented yet the principles of manageable budgeting, such as efficiency, effectivity, transparency and accountability. The majority of finding aspect was in the process of administration in managing of local finance to be performance-based budgeting. The implication on opinion result of audit indicated that in transition era to be improved in budgeting implementation to reach ‘unqualified opinion’. Key words: implication, local budget, opinion, qualified opinion (WDP)